Multiple sclerosis-disease modifying therapies affect humoral and T-cell response to mRNA COVID-19 vaccine - Dominelli, Federica; Zingaropoli, Maria Antonella; Tartaglia, Matteo; Tortellini, Eeva; Guardiani, Mariasilvia; Perri, Valentina; Pasculli, Patrizia; Ciccone, Federica; Malimpensa, Leonardo; Baione, Viola; Napoli, Anna; Gaeta, Aurelia; et al. (Frontiers in Immunology, 2022)
Background: The mRNA vaccines help protect from COVID-19 severity,however multiple sclerosis (MS) disease modifying therapies (DMTs) might affect the development of humoral and T-cell specific response to vaccination. Methods: The aim of the study was to evaluate humoral and specific T-cell response,as well as B-cell activation and survival factors,in people with MS (pwMS) under DMTs before (T0) and after two months (T1) from the third dose of vaccine,comparing the obtained findings to healthy donors (HD). All possible combinations of intracellular IFNγ,IL2 and TNFα T-cell production were evaluated,and T-cells were labelled “responding T-cells”, those cells that produced at least one of the three cytokines of interest,and “triple positive T-cells”,those cells that produced simultaneously all the three cytokines. Results: The cross-sectional evaluation showed no significant differences in anti-S antibody titers between pwMS and HD at both time-points. In pwMS,lower percentages of responding T-cells at T0 (CD4:p=0.0165;CD8: p=0.0022) and triple positive T-cells at both time-points compared to HD were observed (at T0,CD4:p=0.0007 and CD8:p=0.0703; at T1,CD4:p=0.0422 and CD8: p=0.0535). At T0,pwMS showed higher plasma levels of APRIL,BAFF and CD40L compared to HD (p<0.0001, p<0.0001 and p<0.0001, respectively) and at T1, plasma levels of BAFF were still higher in pwMS compared to HD (p=0.0022). According to DMTs, at both T0 and T1, lower anti-S antibody titers in the depleting/sequestering-out compared to the enriching-in pwMS subgroup were found (p=0.0410 and p=0.0047, respectively) as well as lower percentages of responding CD4+ T-cells (CD4:p=0.0394 and p=0.0004, respectively). Moreover, the depleting/sequestering-out subgroup showed higher percentages of IFNγ-IL2-TNFα+ T-cells at both time-points, compared to the enriching-in subgroup in which a more heterogeneous cytokine profile was observed (at T0 CD4:p=0.0187; at T0 and T1 CD8:p=0.0007 and p=0.0077, respectively). Conclusion: In pwMS, humoral and T-cell response to vaccination seems to be influenced by the different DMTs. pwMS under depleting/sequestering-out treatment can mount cellular responses even in the presence of a low positive humoral response, although the cellular response seems qualitatively inferior compared to HD. An understanding of T-cell quality dynamic is needed to determine the best vaccination strategy and in general the capability of immune response in pwMS under different DMT.